Facile fabrication of conductive polyaniline nanoflower modified electrode and its application for microbial energy harvesting. (20th November 2017) - Liu, Xiang; Zhao, Xiaohua; Yu, Yang-Yang; Wang, Yan-Zhai; Shi, Yu-Tong; Cheng, Qian-Wen; Fang, Zhen; Yong, Yang-Chun
Graphical abstract: Highlights: Facile approach for synthesis of conductive polyaniline nanoflower was developed. Modification of carbon cloth electrode with polyaniline nanoflower was achieved. The application of the modified electrode for microbial fuel cells was demonstrated Abstract: A facile strategy for fabrication of conductive polyaniline (PANI) nanoflower modified carbon cloth electrode was developed and its application for microbial energy harvesting was also demonstrated. By simply tuning the concentration of aniline monomer, uniformly distributed PANI nanoflowers assembled from PANI nanoflakes anchored on the surface of carbon cloth electrode were fabricated with in-situ polymerization. Electrochemical and spectral analyses indicated that the synthesized PANI nanoflower was in conductive emeraldine salt form. Electrochemical impedance spectroscopy (EIS) analysis revealed PANI nanoflower modification reduced the charge transfer resistance of carbon cloth electrode, indicating the PANI nanoflower had excellent electrochemical activity. Furthermore, the PANI nanoflower modified electrode was used as the anode of microbial fuel cells (MFC), which delivered 2.6 and 6.5 times higher voltage and power output than these of pristine carbon cloth electrode, respectively. This work provided a controllable synthesis strategy for PANI nanostructure and demonstrated its promise in microbial energy harvesting.